Influencer Marketing Strategies in Increasing Customer Engagement (Tiktok Minke Case Study) - Saputro, Kurniawan Ari; Wahyudi, Tri Nur; Yuningsih, Yuni (Proceedings International Conference on Education Innovation and Social Science, 2023)
The rapid development of technology encourages businesses to use other alternatives in marketing their products, one of which is the use of influencer marketing services. This aims to expand product information and is also key to increasing customer engagement. In increasing customer engagement, influencers need to implement a good strategy so that the desired goals are achieved. Therefore, this research aims to find out the influencer marketing strategy implemented by Adam through minke's TikTok account to increase customer engagement. This research is qualitative in nature using the case study method. In addition, this research collects data through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data reduction and conclusion display. The results of this research indicate that the strategy implemented out by Adam is included in a good influencer strategy, this is indicated by Adam's considerable efforts in increasing his credibility so that the engagement created is high. This research is expected to have an academic impact on influencer marketing strategies in increasing customer engagement as carried out by Adam.